Distinct developmental growth patterns account for the disproportionate expansion of the rostral and caudal isocortex in evolution - Charvet, Christine J. (Frontiers in Human Neuroscience, 2014)
In adulthood, the isocortex of several species is characterized by a gradient in neurons per unit of cortical surface area with fewer neurons per unit of cortical surface area in the rostral pole relative to the caudal pole. A gradient in neurogenesis timing predicts differences in neurons across the isocortex: neurons per unit of cortical surface area are fewer rostrally, where neurogenesis duration is short, and higher caudally where neurogenesis duration is longer. How species differences in neurogenesis duration impact cortical progenitor cells across its axis is not known. I estimated progenitor cells per unit of ventricular area across the rostro-caudal axis of the isocortex in cats (Felis catus) and in dogs (Canis familiaris) mostly before layers VI-II neurons are generated. I also estimated the ventricular length across the rostro-caudal axis at various stages of development in both species. These two species were chosen because neurogenesis duration in dogs is extended compared with cats. Caudally, cortical progenitors expand more tangentially and in numbers in dogs compared with cats. Rostrally, the cortical proliferative zone also expands more tangentially in dogs compared cats. However, the tangential expansion in the rostral cortical proliferative zone occurs without a concomitant increase in progenitor cell numbers. The tangential expansion of the ventricular surface in the rostral cortex is mediated by a reduction in cell density. These different developmental growth patterns account for the disproportionate expansion of the rostral (i.e., frontal cortex) and caudal cortex (e.g., primary visual cortex) when neurogenesis duration lengthens in evolution.